Low-Grade Inflammation and Spinal Cord Injury: Exercise as Therapy?. (5th March 2013) - da Silva Alves, Eduardo; de Aquino Lemos, Valdir; Ruiz da Silva, Francieli; Lira, Fabio Santos; dos Santos, Ronaldo Vagner Thomathieli; Rosa, João Paulo Pereira; Caperuto, Erico; Tufik, Sergio; de Mello, Marco Tulio
Abstract : An increase in the prevalence of obesity in people with spinal cord injury can contribute to low-grade chronic inflammation and increase the risk of infection in this population. A decrease in sympathetic activity contributes to immunosuppression due to the lower activation of immune cells in the blood. The effects of physical exercise on inflammatory parameters in individuals with spinal cord injury have not been well described. We conducted a review of the literature published from 1974 to 2012. This review explored the relationships between low-grade inflammation, spinal cord injury, and exercise to discuss a novel mechanism that might explain the beneficial effects of exercise involving an increase in catecholamines and cytokines in people with spinal cord injury.